2006
DOI: 10.1152/ajprenal.00395.2005
|View full text |Cite
|
Sign up to set email alerts
|

Colonic irritation in the rat sensitizes urinary bladder afferents to mechanical and chemical stimuli: an afferent origin of pelvic organ cross-sensitization

Abstract: Chronic pelvic pain (CPP) disorders frequently overlap. We have demonstrated that acute and chronic colonic irritation can lead to neurogenic cystitis. We hypothesize that acute colonic irritation can sensitize urinary bladder afferents to mechanical and chemical stimuli. Single-unit afferent activity was recorded from fine filaments of the pelvic nerve in urethane-anesthetized Sprague-Dawley female rats before and 1 h after intracolonic administration of trinitrobenzenesulfonic acid (TNBS). Only spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
112
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 35 publications
13
112
0
2
Order By: Relevance
“…As we have recently shown, cross-organ pelvic reflexes, as well as, cross-organ alterations in physiological functioning and sensation following irritation (bladder-to-bowel and vice versa), suggested the involvement of pre-existing dichotomous afferent pathways in the pelvis (Pezzone et al 2005). This putative role of afferent pathways was further verified by single unit recordings of C-fiber bladder afferents within the pelvic nerve that exhibited sensitized mechanical and chemogenic response properties following acute colonic irritation with trinitrobenzenesulfonic acid (TNBS) (Ustinova et al 2006). Moreover, interruption of extrinsic neural input to the bladder ameliorated this effect, further confirming a neurogenic process originating in the colon.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As we have recently shown, cross-organ pelvic reflexes, as well as, cross-organ alterations in physiological functioning and sensation following irritation (bladder-to-bowel and vice versa), suggested the involvement of pre-existing dichotomous afferent pathways in the pelvis (Pezzone et al 2005). This putative role of afferent pathways was further verified by single unit recordings of C-fiber bladder afferents within the pelvic nerve that exhibited sensitized mechanical and chemogenic response properties following acute colonic irritation with trinitrobenzenesulfonic acid (TNBS) (Ustinova et al 2006). Moreover, interruption of extrinsic neural input to the bladder ameliorated this effect, further confirming a neurogenic process originating in the colon.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, interruption of extrinsic neural input to the bladder ameliorated this effect, further confirming a neurogenic process originating in the colon. Thus, it was concluded that bowel-to-bladder, cross-organ afferent sensitization may occur peripherally, via antidromic axon reflexes from a single dichotomizing primary afferent supplying both the bowel and bladder as well as centrally via spinal or supraspinal circuits (Ustinova et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, there is a considerable degree of overlap and interaction between neural pathways to different pelvic organs (eg. rectum and urogenital system) with considerable potential for integration or modulation of their activity within the spinal cord (Berkley, 2006;Pezzone et al, 2005;Rudick et al, 2007;Ustinova et al, 2006;Ustinova et al, 2010).…”
Section: The Enhanced Expression Of C-fos In L3 Preganglionic Neuronsmentioning
confidence: 99%
“…[9][10][11][12] However, a complete understanding of the autonomic control of the human bladder is still elusive. 8,13 The divergent nature of the autonomic nervous system in the pelvic region creates a complex pattern of altered neurophysiology, and evidence has been documented to show the presence of cross-system viscera-visceral interactions, that is, bladder inflammation having a direct influence on uterine or colon contractions/inflammations, and vice versa.…”
Section: Introductionmentioning
confidence: 99%